The Implementation of Integrated Quality Function Deployment (QFD) and SWOT Analysis in the Quality Improvement Strategy of Jackfruit Chips - Rucitra, Andan Linggar (Department of Agro-industrial Technology, University of Brawijaya, 2020)
AbstractQuality is one inseparable attributes that should be noted in fulfilling consumers’ need and expectation. Each product must have certain advantages in order to be able to compete in the market. Customers’ loyalty is the key to sustainable quality improvement. CV X is a business unit located in Malang selling various snack souvenirs products from Malang. This souvenirs shop has become one of the main destinations for shopping snack souvenirs in Malang. Furthermore, jackfruit chips are one of the most popular fruit chips sold by CV X. The increasing popularity of jackfruit chips in the market will affect the quality expected by consumers. Quality Function Deployment (QFD) is one of the most effective tools that can support a company or business unit by creating a response to consumer needs, explaining consumer’s demand toward certain products and determining any process needed to meet consumer’s expectations. The objective of this study is to analyze several attributes that affect consumer satisfaction on jackfruit chips produced by CV X. The results of this study suggest that a product with stable volume is in the first place with the value of 7. Meanwhile, from the data analyzed with Strength Weakness Opportunity Threat (SWOT) Analysis, the result indicates that the product value is on the S-O position, with specific indicators of having a competitive price and market leader.Keywords: jackfruit chips, improvement strategy, quality function deployment